2013
DOI: 10.1890/12-0295.1
|View full text |Cite
|
Sign up to set email alerts
|

Consistency and sensitivity of stream periphyton community structural and functional responses to nutrient enrichment

Abstract: Eutrophication remains one of the foremost impacts of industrialization and population expansion on aquatic ecosystems worldwide. Selecting metrics for assessing the manner in which communities and biogeochemical processes respond to nutrient fertilization is an ongoing management challenge critical both for detecting changes and for monitoring recovery of impaired environments. A key limitation to the selection of response variables is the lack of consistent evaluation of metrics under the same conditions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Sanderson et al (2009) showed that 31.5% of the streams they studied showed no nutrient limitation on periphyton production using the same methods we used. Similarly Nelson et al (2013) found in one of two ecoregions in California they studied, increasing nutrient content did not result in increased chlorophyll a production. The potential causes for the lack of response to increased nutrients could be sufficient nutrients in the stream, other limiting factors such as light, temperature, or disturbance and the presence of invertebrate grazers.…”
Section: Discussionsupporting
confidence: 72%
“…Sanderson et al (2009) showed that 31.5% of the streams they studied showed no nutrient limitation on periphyton production using the same methods we used. Similarly Nelson et al (2013) found in one of two ecoregions in California they studied, increasing nutrient content did not result in increased chlorophyll a production. The potential causes for the lack of response to increased nutrients could be sufficient nutrients in the stream, other limiting factors such as light, temperature, or disturbance and the presence of invertebrate grazers.…”
Section: Discussionsupporting
confidence: 72%
“…The positive relationship between resource availability and measures of food web complexity (e.g., connectance and levels of omnivory; Supporting Information Appendix F) aligns with theoretical predictions of adaptive foraging (Uchida et al ). Specifically, abundant resources can promote higher biomasses in a wide range of potential prey items (e.g., periphyton, algivorous primary consumers; Cardinale et al ; Nelson et al ), thus facilitating adaptive prey‐switching ( sensu Uchida et al ) evident in higher densities of trophic interactions (i.e., connectance) with prey of varying trophic levels (i.e., degree of omnivory). In bridging our empirical observations with food web theory, the findings presented here imply that resource availability favors greater structural complexity by facilitating adaptive feeding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement that a good indicator will consistently detect change across space and time, but will be sufficiently sensitive to respond to changes in environmental factors (Cottingham and Carpenter, 1998; Nelson et al, 2013). The sensitivity of diatoms has been confirmed by the significant relationships between measured proximate environmental variables and diatom indices in this study (Table 3).…”
Section: Discussionmentioning
confidence: 99%